Socio-structural characteristics of intergroup relations and identity management strategies: results from a field study in East Germany - Mummendey, Amélie; Klink, Andreas; Mielke, Rosemarie; Wenzel, Michael; Blanz, Mathias (European journal of social psychology, 1999)
In a field study in East Germany, predictions by Social Identity Theory concerning relations among socio‐structural characteristics of intergroup relations (stability, legitimacy, permeability) and identity management strategies (e.g. social competition) were examined. In general, East Germans were expected to consider their status position as inferior compared to West Germans. Moreover, depending on whether they regard such a status difference as legitimate or illegitimate, as stable or unstable, and whether they perceive group boundaries as permeable or impermeable, East German participants should differ with respect to identity management strategies such as change of status relations, change of categorization, change of comparison dimension, change of comparison object and change of group membership. Five hundred and seventeen participants from different regions of East Germany completed a questionnaire on various aspects of life satisfaction. A path model including stability, legitimacy and permeability as predictors, ingroup identification as mediator and identity management strategies as criteria was tested. Results are mainly in line with assumptions on main effects derived from Social Identity Theory. However, some extensions and clarifications with respect to assimilation situations seem to be adequate. In addition, results show that ingroup identification can be regarded as a powerful mediator between perceived intergroup relations and identity management strategies. Copyright © 1999 John Wiley & Sons, Ltd.